2005
DOI: 10.2472/jsms.54.1225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Charge on Cyclic Stress-Strain Properties and Fatigue Behavior of Carbon Steels

Abstract: Effects of hydrogen charge on fatigue behaviour of two carbon steels, JIS-S10C (SAE1010) and JIS-S45C (SAE1045) were investigated. There was no hydrogen effect in the cyclic stress-strain hysteresis loops of S10C hydrogen-charged with 0.2 ppm. On the other hand, the strain amplitude was decreased in S45C hydrogen-charged with 0.8 ppm. The delayed yielding and the decrease in the saturated value of the strain amplitude were observed in the hydrogen-charged specimen (H : 0.5 ppm) of S45C under the constant stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Figure 33 shows the S-N data for the uncharged and hydrogen-charged 0.47%C steel (Uyama et al, 2004). Figures 34a and b show that there is a clear difference in slip band morphology between the uncharged and hydrogen charged specimen (Uyama et al, 2004). Slip bands in the uncharged specimens (Figure 34a) gradually spread throughout and finally completely covered the ferrite grains with increasing number of cycles.…”
Section: Scm435 Steelmentioning
confidence: 91%
See 2 more Smart Citations
“…Figure 33 shows the S-N data for the uncharged and hydrogen-charged 0.47%C steel (Uyama et al, 2004). Figures 34a and b show that there is a clear difference in slip band morphology between the uncharged and hydrogen charged specimen (Uyama et al, 2004). Slip bands in the uncharged specimens (Figure 34a) gradually spread throughout and finally completely covered the ferrite grains with increasing number of cycles.…”
Section: Scm435 Steelmentioning
confidence: 91%
“…The specimen surface of 0.45%C was finished by electropolishing after the charging. Figure 33 shows the S-N data for the uncharged and hydrogen-charged 0.47%C steel (Uyama et al, 2004). Figures 34a and b show that there is a clear difference in slip band morphology between the uncharged and hydrogen charged specimen (Uyama et al, 2004).…”
Section: Scm435 Steelmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, S10C is adopted not only as the actual material whose chemical composition of S10C is similar to that of pipe-line steel, but also as the material which is suitable for the basic research of the FCG mechanism. It is well-known that hydrogen affects slip behavior (8), (9) . Therefore, it is possible that the grain boundary is damaged (microvoid, microcrack) by slips produced by hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that the IG damage was caused by transgranular slip. It has been reported that hydrogen affects transgranular slip (8), (9) . As in previous studies, hydrogen affects the transgranular slip and the slip easily causes the IG damage.…”
mentioning
confidence: 99%